Editor’s Letter - Gonzalez Alvarado, Tania Elena (Mercados y Negocios, 2024)
Mercados y Negocios is supported by the University of Guadalajara (a Public Institution) by academics and experts who support open science. For this reason, the author of the articles is not charged. Readers are also not charged for access to the content. These actions support the collective construction of a participatory and universal scientific ecosystem. We want research on marketing, international Business, and competitiveness to benefit society and be available to everyone (Redalyc-Amelica, 2023). This issue contains five research articles subjected to the peer-review process.